Behavior of Pipe Piles in Sand Plugging & Pore-Water Pressure Generation During Installation and Loading - Iskander, Magued. (Springer Series in Geomechanics and Geoengineering,, 2011)
One of the major difficulties in predicting the capacity of pipe piles in sand has resulted from a lack of understanding of the physical processes that control the behavior of piles during installation and loading. This monograph presents a detailed blue print for developing experimental facilities necessary to identify these processes. These facilities include a unique instrumented double-walled pipe-pile that is used to delineate the frictional stresses acting against the external and internal surfaces of the pile. The pile is fitted with miniature pore-pressure transducers to monitor the generation of pore water pressure during installation and loading. A fast automatic laboratory pile hammer capable of representing the phenomena that occur during pile driving was also developed and used. Finally, a pressure chamber; feedback control system; data acquisition system; loading frame; sand handling, pluviating, saturating, and drying apparatus have been integrated to allow convenient load testing of piles under simulated field conditions. The experimental apparatus is presented with sufficient details to allow readers to duplicate or modify the design to suit their own needs. A number of load tests were carried out to identify the effects of inertia and build-up of pore water pressure on pile plugging. Continuous measurement of dynamic and static excess pore pressures, frictional and end bearing stresses, and the elevation of the soil inside the pile during installation and loading are presented. The results of the testing program validates the performance of the developed apparatus, and provide unique insights into soil-structure interaction during pile driving and subsequent loading. The work contributes to a better understanding of pile behavior.